Statistical ideas and methods - Jessica M. Utts (Thomson-Brooks/Cole, 2006)
Emphasizing the conceptual development of statistical ideas, STATISTICAL IDEAS AND METHODS actively engages students and explains topics in the context of excellent examples and case studies. This text balances the spirit of statistical literacy with statistical methodology taught in the introductory statistics course. Jessica Utts and Robert Heckard built the book on two learning premises: (1) New material is much easier to learn and remember if it is related to something interesting or previously known; (2) New material is easier to learn if you actively ask questions and answer them for yourself. More than any other text available, STATISTICAL IDEAS AND METHODS motivates students to develop their statistical intuition by focusing on analyzing data and interpreting results as opposed to focusing on mathematical formulation. STATISTICAL IDEAS AND METHODS provides the exciting coverage from the authors' acclaimed MIND ON STATISTICS along with coverage of additional discrete random variables, nonparametric tests of hypotheses, multiple regression, two-way analysis of variance, and ethics